The Changing Face of School Accountability: A Charge to Teacher Educators to Make Radical Changes - Kirsten Limpert; Stuart Ervay (The Advocate, 2013)
Since the No Child Left Behind (NCLB) initiative is being replaced by a much different approach called Common Core Standards (CCS), education’s challenge is to find ways to effectively incorporate the CCS guidelines within local curricula. This paper discusses past, current, and future teacher education as they relate to NCLB and CCS. In addition, four specific recommendations are made as we examine possible features of future teacher preparation programs as they relate to curriculum, instruction, assessment, and academic program decision-making.